Shadows of doubt: stereotypes, crime, and the pursuit of justice - O'Flaherty, Brendan (Harvard University Press, 2019)
Stereotypes -- Crime -- Robbery -- Murder -- Public action -- Police stops -- Use of force -- Lethal force -- Testimony -- Judgment -- Punishment -- Justice -- Conclusion: Hope